An introduction to optimization - Chong, Edwin Kah Pin; Zak, Stanislaw H. (Wiley series in discrete mathematics and optimization, 2013)
"The purpose of the book is to give the reader a working knowledge of optimization theory and methods"--Provided by publisher.